2018
DOI: 10.4049/jimmunol.1700480
|View full text |Cite
|
Sign up to set email alerts
|

Deep Coverage Tissue and Cellular Proteomics Revealed IL-1β Can Independently Induce the Secretion of TNF-Associated Proteins from Human Synoviocytes

Abstract: Synovitis is a key contributor to the inflammatory environment in osteoarthritis (OA) joints. Currently, the biological therapy of OA is not satisfactory in multiple single-target trials on anti-TNF agents, or IL-1 antagonists. Systems biological understanding of the phosphorylation state in OA synovium is warranted to direct further therapeutic strategies. Therefore, in this study, we compared the human synovial phosphoproteome of the OA with the acute joint fracture subjects. We found that OA synovium had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…(30) Studies have con rmed that IL-1β could induce the upregulated secretion of COL3A1 from the human synoviocyte. (31) Our research demonstrated that BZXD could inhibit the expression of IL-1β and COL3A1 is decreased in the BZXD group relative to the CIA group. Thence, COL3A1 may be a molecular marker for BZXD treating RA.…”
Section: Discussionmentioning
confidence: 58%
“…(30) Studies have con rmed that IL-1β could induce the upregulated secretion of COL3A1 from the human synoviocyte. (31) Our research demonstrated that BZXD could inhibit the expression of IL-1β and COL3A1 is decreased in the BZXD group relative to the CIA group. Thence, COL3A1 may be a molecular marker for BZXD treating RA.…”
Section: Discussionmentioning
confidence: 58%
“…Evidence suggests that the expression levels of COL3A1 increased in the early stages of OA and decreased in the later stages (Rai et al, 2019). Tang et al (2018) also discovered that IL-1 increased the protein levels of COL3A1 in synoviocytes. MMP9, also known as gelatinase B, is an enzyme that degrades the ECM components such as collagen, fibronectin, and laminin.…”
Section: Discussionmentioning
confidence: 95%
“…Secretome studies by high-resolution mass spectrometry on primary human synoviocytes, the main cellular components of the synovium, are lacking. Indeed, to date, a phosphoproteomic analysis of synoviocytes has only been reported by Tang and co-workers [37]. In addition, extensive proteomic characterizations have been performed so far on OA synovial fluids [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%